CORN SILK AS GREEN ADSORBENT FOR METHYLENE BLUE DYE REMOVAL - KALIANNAN PALANIWAIL, THEVIN (IRC, 2019)
Malaysia is a fast growing country in south east asia with many developments and industries. This has led to major environmental pollution in the presents days. Lots of industries are using dye and the common industries are textiles and food. Improper disposal of waste water containing residual dyes from these industries into the environments causes many negative effects. The main methods of removing dyes in waste water are chemicals, physicals, and biological method. Adsorption method is a physical method. Low cost biomass adsorbents have become a major area of consideration to many researchers due to the expense nature of the available activated carbon. Although commercial activated carbon is the most sufficient and efficiently used. Biomass is readily available in high amount and it is environment friendly. In this project, corn silk is chosen and studied as the adsorbent in removal of Methylene Blue dye. The main parameters studied is biomass loading, initial dye solution concentrations and solution pH on the dye adsorption using corn silk.